Instructions for sports medicine patients - Safran, Marc R.; Zachazewski, James E.;Stone, David A. (Philadelphia, Pennsylvania : Elsevier, Saunders, 2012)
Presents the combined perspectives of both an orthopaedic sports medicine physician and a physical therapist for a balanced approach to therapeutic practices. This title helps you ensure that your patients comply with therapeutic instructions and recover quickly from chronic ankle instability, tennis elbow, and more.
Keywords: ATHLETIC INJURIES DIAGNOSIS